Sanitary Pad Interventions for Girls' Education in Ghana: A Pilot Study - Montgomery, Paul (Public Library of Science, 2012)
BACKGROUND: Increased education of girls in developing contexts is associated with a number of important positive health, social, and economic outcomes for a community. The event of menarche tends to coincide with girls' transitions from primary to secondary education and may constitute a barrier for continued school attendance and performance. Following the MRC Framework for Complex Interventions, a pilot controlled study was conducted in Ghana to assess the role of sanitary pads in girls' education. METHODS: A sample of 120 schoolgirls between the ages of 12 and 18 from four villages in Ghana participated in a non-randomized trial of sanitary pad provision with education. The trial had three levels of treatment: provision of pads with puberty education; puberty education alone; or control (no pads or education). The primary outcome was school attendance. RESULTS: After 3 months, providing pads with education significantly improved attendance among participants, (lambda 0.824, F = 3.760, p<.001). After 5 months, puberty education alone improved attendance to a similar level (M = 91.26, SD = 7.82) as sites where pads were provided with puberty education (Rural M = 89.74, SD = 9.34; Periurban M = 90.54, SD = 17.37), all of which were higher than control (M = 84.48, SD = 12.39). The total improvement through pads with education intervention after 5 months was a 9% increase in attendance. After 3 months, providing pads with education significantly improved attendance among participants. The changes in attendance at the end of the trial, after 5 months, were found to be significant by site over time. With puberty education alone resulting in a similar attendance level. CONCLUSION: This pilot study demonstrated promising results of a low-cost, rapid-return intervention for girls' education in a developing context. Given the considerable development needs of poorer countries and the potential of young women there, these results suggest that a large-scale cluster randomized trial is warranted. TRIAL REGISTRATION: Pan African Clinical Trials Registry PACTR201202000361337